Comparative Analysis of Investment Performance Between Conventional and Islamic Stocks (A Study of the Jakarta Islamic Index (JII) and Bisnis27 Index in the 2020-2024 Period) - Widiawati, Farradila Echa; Tyas Danarti Hascaryani (Contemporary Studies in Economic, Finance and Banking, 2025)
The rapid expansion of the Islamic capital market in Indonesia has heightened public interest in sharia-compliant investments. The purpose of this research is to compare the investing performance of conventional stocks with Islamic stocks from 2020 to 2024. The measurement used is using the risk adjusted performance method which consists of the sharpe ratio, treynor ratio, and alpha jensen ratio. This research uses samples of JII index as a representatives of sharia stocks and Bisnis27 index as representatives of conventional stocks. The method of analysis uses the mann-whitney u test. The result of this research showed that there is no difference in stock investment performance between conventional stocks and Islamic stocks as measured using the sharpe ratio and treynor ratio. While the alpha jensen ratio there is a difference in stock investment performance between conventional stocks and Islamic stocks.